2020
DOI: 10.1242/jcs.247353
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction triggers a catabolic response in chondrocytes via ROS-mediated activation of the JNK/AP1 pathway

Abstract: Mitochondrial function is impaired in osteoarthritis (OA) but its impact on cartilage catabolism is not fully understood. Here, we investigated the molecular mechanism of mitochondrial dysfunction-induced activation of catabolic response in chondrocytes. Using cartilage slices from normal and OA cartilage, we show that mitochondrial membrane potential was lower in OA cartilage which was associated with increased production of mitochondrial superoxide and catabolic genes (IL-6, COX-2, MMP-3,-9,-13 and ADAMTS5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…SLI can upregulate protein and mRNA expression of MyHC, MyoG, and MyoD and downregulate the protein and mRNA expression of Mstn and MAFbx (Figures 5(c) – 5(e) ); the downregulation of ERK phosphorylation and upregulation of JNK phosphorylation in C2C12 myotube cells resulted in the incorporation of FoxO3 into the nucleus (Figures 5(f) and 5(g) ). Because the JNK pathway is related to the AP-1 pathway [ 49 ], we verified the effects of the AP-1 pathway on C2C12 myotube cells. The AP-1 pathway inhibitor T-5224 was applied to C2C12 myotube cells, and the expression of c-Fos was detected to verify the efficacy of the inhibitor [ 50 ] in the NC group, T-5224 group, DDP + T-5224 group, and DDP groups.…”
Section: Resultsmentioning
confidence: 99%
“…SLI can upregulate protein and mRNA expression of MyHC, MyoG, and MyoD and downregulate the protein and mRNA expression of Mstn and MAFbx (Figures 5(c) – 5(e) ); the downregulation of ERK phosphorylation and upregulation of JNK phosphorylation in C2C12 myotube cells resulted in the incorporation of FoxO3 into the nucleus (Figures 5(f) and 5(g) ). Because the JNK pathway is related to the AP-1 pathway [ 49 ], we verified the effects of the AP-1 pathway on C2C12 myotube cells. The AP-1 pathway inhibitor T-5224 was applied to C2C12 myotube cells, and the expression of c-Fos was detected to verify the efficacy of the inhibitor [ 50 ] in the NC group, T-5224 group, DDP + T-5224 group, and DDP groups.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported mitochondrial dysfunction, including mitochondrial respiratory chain enzyme complex activities and membrane potential, in chondrocytes of OA patients ( 9 ). Mitochondrial dysfunction leads to cartilage degeneration by suppressing ATP production, depolarizing the mitochondrial membrane, increasing oxidative stress, disrupting calcium homeostasis, and altering mitochondrial DNA ( 10 11 12 13 ). Mitochondrial dysfunction has been reported in OA chondrocytes, inducing an imbalance between anabolism and catabolism of extracellular matrix ( 14 15 ) and decreasing mitochondrial complex activity ( 16 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of several of these metalloproteinases, as well as pro-inflammatory mediators, is induced by mechanical destabilization of the joint [ 9 ]. Additional factors including chondrocyte senescence [ 11 ], oxidative stress [ 12 , 13 , 14 , 15 ], and/or inflammation can also increase metalloproteinase expression and tip the balance towards cartilage breakdown.…”
Section: Introductionmentioning
confidence: 99%